A uniform supply chain management framework for oil and gas sector: a preliminary review - Alhosani, Adel; Mohamed Zabri, Shafie (IASE, 2018)
The multidisciplinary nature of the oil and gas sector makes Supply Chain Management (SCM) practices in this sector more complex. Moreover, lack of generic model/framework results in lack of sharing knowledge, training, proper model or framework, and add additional complexities to SCM in oil and gas sector. Furthermore, the SCM knowledge of oil and gas sector is scattered in internet, books, thesis, journals papers, conference’s papers, online database, and organizations. It lacks the obvious structure to unify, facilitate, reuse, and manage that scattered knowledge. Thus, it receives little attention from researchers. Current researchers have not focused on fundamental and essential guidelines to establish a baseline for SCM in oil and gas sector. This paper identifies and proposes common SCM practices concepts in oil and gas sector to unify the view of SCM practices in the form of a conceptual framework that can be seen as a baseline for this domain. The framework will be validated and refined to assist as a representational layer to unify, facilitate, and expedite the access to SCM practices in oil and gas sector. The specific aims are to facilitate knowledge sharing, combining